Therapeutic capabilities of secnidazole in the treatment of bacterial vaginosis - Yu.E. Dobrokhotova; P.A. Shadrova (РМЖ. Мать и дитя, 2022)
Yu.E. Dobrokhotova, P.A. Shadrova Pirogov Russian National Research Medical University, Moscow, Russian Federation Background: the research is still focused on bacterial vaginosis (BV) in view of its high prevalence among women and potential damaging effects on fertility. The treatment regimens which are presented in the current guidelines and available for obstetricians and gynecologists may cause adverse local and systemic effects. In addition, female patients frequently experience BV recurrences. Aim: to assess the efficacy of taking secnidazole once as a single dose in the treatment of BV based on clinical findings and laboratory-based test results. Patients and Methods: the study included 40 female patients with diagnosed BV. The patients were split into two groups, 20 women in each group. The treatment group patients received secnidazole 2 g once as a single dose, and the control group patients received the standard treatment with metronidazole 500 mg twice daily for 7 days. The evaluation of patients included the vaginal pH value and laboratory-based diagnostic tests, such as microscopy of the vaginal discharge and Florocenosis/Bacterial vaginosis-FRT PCR assay whose prognostic value indicators are comparable with the international clinical and laboratory-based diagnostic criteria. Results: before therapy, the mean leucocyte count in the vaginal smear in the treatment group patients was 12.4±3.0 per field of vision and in the control group patients — 11.3±1.8; after therapy — 9.2±1.2 and 10.1±4.4, respectively. A statistically significant decrease (р<0.05) in vaginal pH was recorded after the therapy: to 4.4±0.1 in the treatment group and 4.3±0.1 in the control group. The average concentration of BV-associated species after the administered therapy was lower than that at the baseline (the difference was statistically significant). Conclusion: сonsidering the comparable clinical and microbiological outcomes of the alternative and standard BV treatment regimens, as well as the convenience of administration associated with single-dose therapy, secnidazole can be used to treat bacterial vaginosis. Keywords: bacterial vaginosis, microbiota, pelvic inflammatory disease, secnidazole, metronidazole. For citation: Dobrokhotova Yu.E., Shadrova P.A. Therapeutic capabilities of secnidazole in the treatment of bacterial vaginosis. Russian Journal of Woman and Child Health. 2022;5(4):297–302 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-297-302.